PCR-RFLP Detection od PAI-2 Gene Variants: Prevelence in Ethnic Groups and Disease Relationship in patients Undergoing corony Angiography - Foy, Carole A; Grant, Peter J (Thrombosis and Haemostasis, 1997)
PAI-2 is a fibrinolytic inhibitor produced predominantly by monocytes. Most PAI-2 is intracellular making study in clinical conditions difficult. Abnormalities in production may be associated with inflammation and fibrinolysis at sites of tissue damage such as the atherosclerotic plaque.PAI-2 gene variants have been described: variant A consists of Asn120, Asn404 and Ser413 and variant B consists of Asp120, Lys404 and Cys413. We designed a PCR-RFLP assay using primers spanning the region containing Asn/Lys404 and Ser/Cys413. Variant B contains an Mwol restriction site. We analysed 302 Pima Indians and 286 healthy Caucasian volunteers. To investigate relationships between genotype and vascular disease we analysed 333 Caucasian patients undergoing coronary angiography.Gene variant B was more common in the Pimas than in Caucasians (p <0.0001). There was no significant difference in genotype distribution between the volunteers and patients. In the patients there was no association between genotype and either a history of MI or extent of coronary atheroma.